Anesthetic Management in Preeclampsia Patients with Thalassemia Minor B: A Case Report - Dyatmika, Kadek Dwipa; Tjahya Aryasa; Otniel Adrians Labobar (HM Publisher, 2023)
Introduction: One of the complications of anesthesia that can be encountered in thalassemia patients is cardiovascular instability caused by chronic anemia, cardiomyopathy, and endocrinopathy. In addition, patients with preeclampsia may also experience postoperative risks such as sustained hypertension, stroke, venous thromboembolism, and seizures. This case report will discuss the anesthetic management of pregnant women with preeclampsia and β thalassemia minor. Case presentation: The patient is a pregnant woman G6P0141, 34 weeks gestation, with preeclampsia and a history of minor β thalassemia without therapy. Patients with thalassemia minor are often asymptomatic before pregnancy, but physiological changes during pregnancy can contribute to anemia during pregnancy. Beta thalassemia minor is also associated with an increased incidence of hypertension in pregnancy. Neuraxial anesthesia is recommended in preeclamptic patients to avoid severe hypertension and has a protective effect against postoperative apnea in premature infants. Conclusion: Anesthetic management in asymptomatic patients with minor thalassemia is not much different from normal pregnant women. The risk of bleeding needs special attention, especially in thalassemia patients who have anemia. In patients with preeclampsia, neuraxial anesthesia is preferred over general anesthesia. Postoperative patient care is carried out in an obstetric high dependency unit (OHDU). The patient went home after being treated for 3 days without complications at the hospital.